Physical chemistry of biological interfaces: generic and specific roles of soft interlayers - Tanaka, Motomu; Schneck, Emanuel; Yoshikawa, Hiroshi; Rossetti, Fernanda (Chemistry, 2011)
Nature defines the spatial boundaries between different phases using membranes, and the interfacial interactions are mediated by soft biopolymer interlayers that contain various carbohydrates. This Review provides a comprehensive overview on the interplay of generic and specific interactions at cell-cell and cell-tissue interfaces. A focus will be put on the combination of defined model systems, experimental techniques in real- and reciprocal space, and theoretical simulations.